A Preliminary Account of the Diatom Flora of Koria, Chhattisgarh - Sirmour, R.; Naik, M.L.; Goutam, M.P. (Our Nature, 2013)
Water bodies contain a large number of microorganisms, like bacteria, algae, protozoa etc. Algae are the one of the very important group of the organisms. Diatoms are the well known water planktons belonging to family Bacillariophyceae (Hendy, 1980). Diatom flora of koria was observed by using acid digestion method. The present account is based on the collection of about 5 water samples from different place of koria. 18 species from 11 genera were identified from these collection sites; the genera include Achnanthes, Amphora, Cymbella, Eunotia, Fragilaria, Gomphonema, Hantizschia, Navicula, Nitzschia, Stauroneis and Synedra. DOI: http://dx.doi.org/10.3126/on.v10i1.7782